PENGARUH BRAND AMBASSADOR, BRAND IMAGE, DAN PRODUCT QUALITY TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE MS GLOW DI KABUPATEN JEMBER - Hasanah, Arifatul; Setyowati, Trias; Nursaidah, Nursaidah (Growth, 2023)
This study aims to determine whether there is an influence of brand ambassador, brand image, and product quality on purchasing decisions of MS Glow skincare products in Jember Regency. The population used in this study are consumers in the Jember Regency area who make purchases and use MS Glow skincare products. The sampling technique in this study used purposive sampling with a total sample of 80 respondents. The data collection method uses a questionnaire that is distributed online to buyers and users of MS Glow skincare products. The analytical technique used in this study is multiple linear regression with SPSS 25 (Statistical Product and Service Solution) application tools. The results of statistical testing of respondents based on gender, it is known that male respondents are 17 respondents with a percentage of 21.3% while respondents with female sex are 63 with a percentage of 78.8%. It can be concluded that there are more female respondents. Because most of those who use MS Glow skincare products for facial care tend to be used by women. The results of statistical testing of respondents based on age, it is known that respondents aged 17-22 years amounted to 51 respondents with a percentage of 63.8%. Age 23-28 years jumalh 23 respondents with a percentage of 28.8%. There are 3 respondents aged 29-34 years with a percentage of 3.8%. While the age> 35 years amounted to 3 respondents with a percentage of 3.8%. It can be concluded that the majority of respondents are aged 17-22 years because the average user of MS Glow skincare products in Jember Regency is dominated by young people and students. The results of statistical testing of respondents based on work, it is known that the respondents as students amounted to 48 respondents with a percentage of 60.0%. Respondents who were still students amounted to 8 respondents with a percentage of 10.0%. Respondents who worked as employees amounted to 8 respondents with a percentage of 10.0%. Self-employed amounted to 8 respondents with a percentage of 10.0%. Meanwhile, there are 8 households with a percentage of 10.0%. It can be concluded that the majority of respondents by occupation are dominated by students. The test results show that the coefficient of determination (R2) is 0.680 or 100%. So it can be said that 68% of purchasing decisions are influenced by brand ambassadors, brand image, and product quality, and 32% are influenced by other factors. The test results of multiple linear regression analysis show that the brand ambassador, brand image, and product quality variables have a positive and significant effect on purchasing decisions. This shows that the hypothesis in this study is accepted. This research has implications for companies in making policies and preparing strategies. Several strategies that can be developed by the company are using brand ambassadors as a promotional tool to promote their products, form and create a good brand image, attractive, easily recognizable, and easy to remember by consumers, and continue to innovate to improve product quality and quality.